The Brown Alga Bifurcaria bifurcata Presents an Anthelmintic Activity on All Developmental Stages of the Parasitic Nematode Heligmosomoides polygyrus bakeri - Morgane Miclon; Élise Courtot; Fabrice Guégnard; Océane Lenhof; Leslie Boudesocque-Delaye; Maria Matard-Mann; Pi Nyvall Collén; Philippe Castagnone-Sereno; Cédric Neveu (Pathogens, 2023)
The current control of gastrointestinal (GI) parasitic nematodes mainly relies on the widespread use of anthelmintics, which has inevitably led to resistance. Therefore, there is an urgent need to find new sources of antiparasitic compounds. Macroalgae represent a rich source of active molecules and are widely described as having medicinal properties. In the present study, we investigated the potential anthelmintic activity of aqueous extracts from three species of algae (Bifurcaria bifurcata, Grateloupia turuturu and Osmundea pinnatifida) on the murine parasite Heligmosomoides polygyrus bakeri. Using a set of complementary in vitro tests, including larval development assays, egg hatching tests and nematicidal activity assays on larvae and adults, we report the nematicidal activity of aqueous extracts of B. bifurcata. In addition, aqueous extract fractionation using liquid/liquid partitioning with a solvent of increasing polarity was performed in order to identify the groups of active molecules underlying the anthelmintic activity. Non-polar extracts (heptane, ethyl acetate) demonstrated high anthelmintic potential, highlighting the role of non-polar metabolites such as terpenes. Here, we highlight the strong anthelmintic potential of the brown alga B. bifurcata on a mouse model of GI parasites, thus confirming the strong interest in algae as natural alternatives for the control of parasitic nematodes.